EXPERIMENTAL STUDY OF CONSTRUCTION OF INTEGRATED PHOTO AND PHOTOHEAT EXCHANGE SYSTEMS. - Komilov, Asliddin; Nasrullayev, Yusuf; Ergashev, Shaxriyor (Innovatsion texnologiyalar, 2024)
Using a solar simulator, a photoelectric-thermal system integrated into an open-loop air building with a working fluid was experimentally investigated. Options for building-integrated photovoltaic/thermal systems and systems using polycrystalline silicon photovoltaic panels were explored. Options for building-integrated photovoltaic/thermal systems and systems using polycrystalline silicon photovoltaic panels were explored. Experimental results show that the efficiency of equivalent system and PV panels in building-integrated PV/thermal systems, the bottom surface in the cavity of building-integrated PV/thermal system sometimes achieves high thermal efficiency due to solar radiation absorption. There are various ways to solve this problem, and the Solar Simulator creates accurate and repeatable test conditions in terms of solar radiation, wind speed and ambient temperature, allowing the prototype to be tested in a stable, near-room temperature environment. Lamps that simulate sunlight under stable conditions produce radiation close to the solar spectrum. The fan creates winds of varying speeds parallel to the surface of the PV panel in the same direction as the current in the cavity. Thermal efficiency of the insulating layer, which supports the structure of the integrated photovoltaic/thermal systems of the building, at an angle of inclination from 0 to 180 degrees, the solar radiation drop in the simulator is from 880 to 940 W/m2 , the average wind speed is from 2 to 3 m/ s. Theoretical and experimental studies were carried out to determine the change in the temperature of the air passing through a system with a photo and photoheat exchanger, taking into account room temperature and the radiation intensity of the solar simulator.